NON-STANDARD TASKS AS A MEANS OF ACTIVATION ACTIONS OF JUNIOR SCHOOLCHILDREN (Pedagogy of Higher and Secondary Education, 2004)
The peculiarity of using the utraditional tasks to activate junior pupils studying in innovation teaching technology are examined in the article.